Cinnamic Acid Derivatives Acting against Aspergillus Fungi. Taq Polymerase I a Potential Molecular Target - Gutierrez, Lucas Joel (2012)
Some members of a series of cinnamic acid derivatives possess promising inhibitory activities in cellular assays against fungi of the Aspergillus genus. In order to search for a possible molecular target of such compounds, their role as Taq polymerase I inhibitors was studied. Four of the compounds studied displayed IC50 values within the range of those considered active as DNA polymerase inhibitors when searching for new cytotoxic molecules. The results obtained in our molecular modeling study appear to show that the inhibitory activity depends on the presence of a stabilizing interaction between the phenylpropanoid derivatives and the residues Asp610, Thr664, Phe667, Tyr671, and Asp785 located in the active site of Taq polymerase I. Also, it is possible to assert that the polymerization of DNA would be the molecular target of cinnamic acid derivatives with antifungal activity, which correlates with the inhibition of Taq polymerase I and the quantitative descriptor for the lipophilia (ClogP).